Aklan National College of Fisheries an institutional case study - Bantigue, Leonor (Magno) 1942- (s.n.], 1971)
This study aimed to provide an empirical description of the Aklan National College of Fisheries.Data were gathered from analysis of school forms and records, memoranda, circulars, general letters, telegrams and other documents from the Bureau of Vocational Education, service manual, budget proposals and other forms of communications sent to the Bureau of Vocational Education. Data reported were focused on the school's mandated tasks, organization and administration, resources, and curricular offerings.